The influence of Charles Baudelaire in Spanish modernismo - Hambrook, Glyn (1985)
Existing critical response to the question of Baudelaire's influence is confined almost exclusively to isolated assumptions articulated by critics who make little attempt, if any, to substantiate their claims, and who, thereby, show scant regard for the burden of proof associated with the study of causal influence. This study proposes to test the validity of such assumptions, and to formulate a more structured appraisal of the issue than has been made hitherto. To this end, it has sought to assemble pertinent evidence and to assess its value as an indication of a real literary debt. Enquiry is structured accordingly. The thesis begins with an exploration of methodological considerations designed to establish the conceptual basis of enquiry (Part One). It then proceeds to study the diffusion of Baudelaire's work in Spain between 1857 and 1910, and, subsequently, to examine critical reaction to the poet during the same period (Part Two). Finally, it studies the theme of Baudelaire's influence in modernismo with reference to the work of six poets whose work is representative of or which, in one case, prefigures the modernista movement in Spain: Manuel Reina, Rubén Darío, Francisco Villaespesa, the brothers Machado and Juan Ramón Jiménez. The particular objective of each case study varies according to the evidence available and the extent of existing critical response, but basically these objectives are three in number. First, to analyse unequivocal influences. Second, to ascertain, where no conclusive proof of influence exists, the extent to which the possibility of influence may be entertained. Third, to indicate, where pertinent, that the question merits more detailed examination than is possible in a general survey of this kind. The study concludes that although Baudelaire's work was reasonably well-diffused, his direct influence was slight and can be proven far less than existing preemptory claims suggest.